(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article addresses the integration of environmental monitoring and occupational safety systems at energy enterprises. It examines modern technologies such as IoT and Big Data, which enable the creation of a unified information system for real-time tracking of environmental conditions and workplace safety. The main directions for implementing advanced integrated technologies in environmental monitoring and occupational safety systems are identified. The study analyzes current safety trends during the adoption of modern safety technologies. It also highlights the risks and advantages of such integrations, using examples from Ukrainian practice.